Within the frame : the journey of photographic vision - DuChemin, David (New Riders, 2016)
"Within the Frame (2009) received critical recognition for its humanity and practical teaching, and in this revision of his classic best-selling book, David duChemin encourages you to search for what matters to you and not give up until you convey it through your photography: 'Im chasing my vision, and you will chase yours in the places best suited to that. Whats important is that you chase that vision intentionally and with passion, refusing to let it be anything but yours and yours alone.' Through a heartfelt discussion about creating photographs of people, places, cultures, and the discovery of a personal point of view that makes those stories compelling and authentic, David teaches how to seek and serve your creative vision through the art of photography by highlighting images from his adventures around the world. Regardless of the setting, its the lessons about the central role of vision and expression in photography that sets this book apart, even if you never wander far from home. David shares the nuances of approaching different subjects, the value of scouting locations (and wandering in unfamiliar places), techniques for photographing landscapes, how to capture a sense of place and culture with sensitivity through images of food, festivals, art and faith, and more. This edition includes new images, creative exercises, updated chapters, a streaming companion video, and discussions about changing perspectives, including an increased focus on landscape photography. Most importantly, David maintains the crucial theme of visionand he helps you find, cultivate, and pursue your own, and then fit it within the frame."--